ESTUDO DE PALINOFÁCIES NA SUCESSÃO RICA EM MATÉRIA ORGÂNICA DA FORMAÇÃO TREMEMBÉ NO POÇO TMB-3-SP (OLIGOCENO DA BACIA DE TAUBATÉ) - Maas, Elayne Cristina Andrade de Sousa; Brito, Marco; Bergamaschi, Sérgio; Mendonça, Joalice (Geochimica Brasiliensis, 2020)
In order to show how the upper part of the Tremembé Formation evolved in terms of organic matter and paleoenvironment types, palynofacies of 20 samples from the TMB-3-SP well were analyzed and sedimentological and geochemical data from the same samples were revisited. The association of the palynofacies data with the total organic carbon, hydrogen index and sedimentological data made it possible to group the studied samples in nine sets, named from 1 to 9, from the bottom to the top of the Tremembé Formation. Sets 1, 3, 5, 7, and 9 represent low water depth phases in the lake, while sets 2, 4, 6, and 8 represent high water depth phases in the lake, with Set 6 witnessing the period with thickest and most expanding water depth of the lake. The phases of low water depth in the lake have lower concentrations of fluorescent amorphous organic matter and predominance of Pediastrum algae over Botryococcus algae. In contrast to the phases of high water depth in the lake, with higher concentrations of fluorescent amorphous organic matter and predominance of Botryococcus algae over Pediastrum algae. Parallel to the knowledge of the stratigraphic distribution of the microscopic characteristics of organic matter along the upper part of the Tremembé Formation in the central region of the Taubaté Basin, the new data constitute important paleoenvironmental indicators.